Answer:
By a quick online search I've found that the expression is:
6*(3x + 8) + 32 + 12*x
We want to use properties to write expressions for the length of the other sides of the square.
Remember that the length of all the sides in a square is the same, so we only need to rewrite the above expression in two different ways.
First, we can use the distribute property in the first term:
6*(3x + 8) + 32 + 12*x
= 6*3x + 6*8 + 32 +12*x
= 18*x + 48 + 32 + 12*x
So this can be the length of one of the sides.
Now we can keep simplifying the above equation:
18*x + 48 + 32 + 12*x
To do it, we can use the distributive and associative property in the next way:
18*x + 48 + 32 + 12*x
= 18*x + 12*x + 48 + 32
= (18*x + 12*x) + (48 + 32)
= (18 + 12)*x + 80
= 30*x + 80
This can be the expression to the other side.